Neo-Sufism in 19th-Century Indonesia: A Critical Examination of Shaikh al-Nawawi al-Bantani's Tanqîḥ al-Qawl. - Nur Hadi Ihsan; Zalfaa' 'Afaaf Zhoofiroh; Bayu Sunarya (Jurnal Ushuluddin, 2026)
The concept of Neo-Sufism has been widely discussed in Islamic studies as an attempt to reconcile Sufi spirituality with Islamic orthodoxy and socio-moral engagement. This article examines the characteristics of Neo-Sufism in Shaikh al-Nawawi al-Bantani’s Tanqīḥ al-Qawl. Employing qualitative library research with a descriptive-analytical method, the study analyzes selected themes in the text, including remembrance (dhikr), repentance (tawbah), poverty (faqr), and silence (ṣamt), using Fazlur Rahman’s concept of Neo-Sufism as an analytical framework. The findings reveal that al-Nawawi integrates spiritual purification with adherence to the Qur’an and Hadith while emphasizing ethical discipline and moral responsibility. His interpretation of Sufi teachings reflects an effort to harmonize inner spirituality with orthodox religious commitments. This study contributes to the scholarship on Southeast Asian Islam by demonstrating how a prominent Jawi scholar reformulated classical Sufi teachings within a scriptural and socio-moral framework characteristic of Neo-Sufism